Accelerating the net-zero economy with CO2-hydrogenated formic acid production: Process development and pilot plant demonstration - Kim, Changsoo; Park, Kwangho; Lee, Hyeonggeon; Im, Jaehyung; Usosky, Denis; Tak, Kyungjae; Park, Damdae; Chung, Wonsuk; Han, Donggu; Yoon, Jieun; Lee, Heewon; Kim, Hyunyoung; et al. (CELL PRESS, 2024)
A process capable of large-scale formic acid (FA) production via CO2 hydrogenation is presented. This study provides the key strategies for use in developing a viable process for continuous operation. Based on the proposed strategies, a pilot-scale process with a capacity of 10 kg/day was constructed. The continuous operability of the process is demonstrated via pilot plant operation for >100 h, achieving a CO2 conversion rate of 82% and producing FA with a high purity of >92 wt %. Techno-economic analysis and life cycle assessment results of the validated simulation model indicate that the proposed process significantly reduces the level of global warming impact by 42% while cutting the production cost by 37%, compared with the conventional process for producing FA. The contents of this study provide a comprehensive manual for developing a viable CO2 utilization solution, showing economic profitability as well as environmental impact reduction.